Students’ Arabic Prokem in the Modern Islamic School Environment - Zamzam Nurhuda; M. Wildan Wildan; Yasir Mubarok (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The phenomena of using Arabic language in modern Islamic boarding schools can be various since Individuals in contemporary Islamic schools tend to communicate in Arabic for formal and informal occasions, like in Gontor, East Java, a modern Islamic boarding school. The variations of using Arabic language in Gontor can be called Arabic prokem. This problem results from the interaction of speakers from various backgrounds and environments. At the same time, those circumstances make the Arabic prokem in Gontor unique for its dialect. Therefore, library research is applied in this qualitative study using qualitative descriptive as the method. The data were collected from Bahasa Arab Khas Gontor, a book by Hisyam Zaini. This book clearly describes words, sentences, forms, and expressions spoken out by students in Gontor. The result of the study shows that the Arabic prokem used by students in Gontor comes from Indonesian vocabulary, the Arabic prokem is delivered in the form of interjection, the Arabic prokem has the changes of phoneme, and the Arabic prokem has Dhamîr pattern.